Modelling of the fracture toughness anisotropy in fiber reinforced concrete (Fracture and Structural Integrity, 2015)
Steel fiber reinforced concrete is potentially very promising material with unique properties, which currently is widely used in some applications, such as floors and concrete pavements. However, lack of robust and reliable models of fiber reinforced concrete fracture limits its application as structural material. In this work a numerical model is proposed for predicting the crack growth in fiber reinforced concrete. The mixing of the steel fibers with the concrete usually creates nonuniform fibers distribution with more fibers oriented in horizontal direction, than in vertical. Simple numerical models of fiber reinforced concrete require a priori knowledge of the crack growth direction in order to take into account bridging action of the fibers, which depends on the fibers orientation. In proposed model user defined elements are used to calculate the bridging force during the course of the analysis when the crack starts to grow. Cohesive elements were used to model the crack propagation in the concrete matrix. In cohesive zone model the cohesive elements are embedded between all solid elements to simulate the arbitrary crack path. The bridging effect of the fibers are modeled as nonlinear springs, where the stiffness of the springs is defined from experimentally measured pull-out force and the angle between the fiber and crack opening direction.
Keywords: Fiber reinforced concrete; Fracture; Cohesive elements